Research of Hamming weight-based algebraic side-channel attack on LED - Ke-ke JI; Tao WANG; Shi-ze GUO; Xin-jie ZHAO; Hui-ying LIU (Tongxin xuebao)
Abstract:The security of LED against the algebraic side-channel attack (ASCA)was evaluated, which is a lightweight block cipher proposed in CHES 2011.Firstly, the attack model of ASCA was analyzed, and then the design and algebraic representations of LED were described. Secondly, the power leakages of LED on ATMEGA324P microcontroller were measured by a digital oscilloscope; some leakage points with obvious power patterns were chosen as the targeted points and used to deduce the Hamming weight via computing the Pearson correlation factor; satisfiability-based, Pseu-do-Boolean optimization-based, linear programming-based methods were used to representing Hamming weights with algebraic equations. Finally, the CryptoMinisat and the SCIP solver were applied to solve for the key and many attacks are conducted under different scenarios. Experiment results demonstrate that LED is vulnerable to ASCA, full 64 bit master key can be derived via analyzing the HW leakages of the first round in LED.